3-D Technology Used to Accurately Understand Equine Ileocolonic Aganglionosis - Muniz, Eliane; Lobo Ladd, Aliny A. B.; Lobo Ladd, Fernando V.; Silva, Andrea A. P. da; Kmit, Fernanda V.; Borges, Alexandre Secorun [UNESP]; Teixeira, Raffaella [UNESP]; Mota, Ligia S. L. S. da [UNESP]; Belli, Carla B.; Zoppa, Andre L. V. de; Silva, Luis C. L. C. da; Melo, Mariana P. de; et al. (Karger, 2013)
Ileocolonic aganglionosis (ICA) is the congenital and hereditary absence of neurons that constitute the enteric nervous system and has been described in various species including humans - Hirschsprung's disease - and horses - overo lethal white syndrome (OLWS). Hirschsprung's disease affects circa 1 in 5,000 live births. At best, this disease means an inability to absorb nutrients from food (humans). At worse, in horses, it always means death. Despite our general understanding of the functional mechanisms underlying ICA, there is a paucity of reliable quantitative information about the structure of myenteric and submucosal neurons in healthy horses and there are no studies on horses with ICA. In light of these uncertainties, we have used design-based stereology to describe the 3-D structure - total number and true size of myenteric and submucosal neurons in the ileum of ICA horses. Our study has shown that ICA affects all submucosal neurons and 99% of nnyenteric neurons. The remaining myenteric neurons (0.56%) atrophy immensely, i.e. 63.8%. We believe this study forms the basis for further research, assessing which subpopulation of myenteric neurons are affected by ileocolonic aganglionosis, and we would like to propose a new nomenclature to distinguish between a complete absence of neurons aganglionosis and a weaker form of the disease which we suggest naming 'hypoganglionosis'. Our results are a step forward in understanding this disease structurally. (C) 2013 S. Karger AG, Basel
Keywords: Ileocolonic aganglionosis; Overo lethal white syndrome; Myenteric plexus; Submucosal plexus; Horses; Stereology